INTERNATIONAL TRADE POLICIES AND MARKETS - Enea Qose; Rezart Dibra (Agora International Journal of Economical Sciences (AIJES), 2023)
In this paper, is presented an overview of the evolution of international trade, emphasizing its role in enabling the international division of labor and a brief examination between Albania and Western Balkan countries foreign trade. The development of foreign trade is intrinsically linked to liberalization, which, in turn, fosters connectivity and mutual economic interdependence among nations. The performance exhibited in both exports and imports plays an important role in fostering sustainable development within the country's economy. Active engagement in these initiatives broadens Albania economy specialization possibilities but, simultaneously, necessitates a commitment to enhancing competitiveness. This development has been shaped by economic, social, political, and cultural factors, with significant advancements in recent decades due to industrialization, advanced transportation, globalization, and the emergence of multinational corporations. Trade indicators for each country serve as a reflection of economic development and mutual benefit. The international markets of foreign countries serve as platforms for both generating additional income through exports and fulfilling the domestic economy's requirements through imports.
Keywords: 330